2013
DOI: 10.1002/smll.201203156
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐Emitting Quantum Dot‐Encoded Microbeads through Membrane Emulsification for Multiplexed Immunoassays

Abstract: NIR-emitting CdSeTe/CdS/ZnS core/shell/shell QD-encoded microbeads are combined with common flow cytometry with one laser for multiplexed detection of hepatitis B virus (HBV). A facile one-pot synthetic route is developed to prepare CdSeTe/CdS/ZnS core/shell/shell QDs with high photoluminescence quantum yield and excellent stability in liquid paraffin, and a Shirasu porous glass (SPG) membrane emulsification technique is applied to incorporate the QDs into polystyrene-maleic anhydride (PSMA) microbeads to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…3(b), a 3D barcode library based on FL1-FL4-FS signals of a flow cytometer (Beckman Coulter FC500) was generated by incorporating 520 nm QDs and 680 nm QDs into differentially-sized polymer microspheres. 30 NIR (near-infrared) QDs (650–800 nm) with wide PL spectra (FWHM > 50 nm) can also be utilized, and a “single wavelength” encoding method 66 was developed to take advantage of QDs in the NIR region. With this method, the spectra of NIR QDs span over FL4 and FL5 fluorescent channels of the flow cytometer.…”
Section: Spectrometrically or Optically Encoded Microspheres With mentioning
confidence: 99%
See 2 more Smart Citations
“…3(b), a 3D barcode library based on FL1-FL4-FS signals of a flow cytometer (Beckman Coulter FC500) was generated by incorporating 520 nm QDs and 680 nm QDs into differentially-sized polymer microspheres. 30 NIR (near-infrared) QDs (650–800 nm) with wide PL spectra (FWHM > 50 nm) can also be utilized, and a “single wavelength” encoding method 66 was developed to take advantage of QDs in the NIR region. With this method, the spectra of NIR QDs span over FL4 and FL5 fluorescent channels of the flow cytometer.…”
Section: Spectrometrically or Optically Encoded Microspheres With mentioning
confidence: 99%
“…However, it was found that iron oxide nanocrystals decreased QD fluorescence intensities by absorbing excitation light and QD fluorescence emissions. 13 NIR-emitting QDs and Fe 3 O 4 nanoparticles were capsulated into PSMA microspheres 66 resulting in a similar decrease in fluorescence intensity, but to a lesser extent than visible light-emitting QDs due to the minimal NIR absorption of magnetic nanoparticles. Jun et al 125 coated SERS dots onto magnetic microspheres to produce magnetic SERS barcodes.…”
Section: Magnetic Nanoparticle-based Suspension Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…The coating of the microbeads with CRA1 was based on the previously published method (23). The coating of the microbeads with CRA1 was based on the previously published method (23).…”
Section: Cytometric Bead Immunoassay Of Sfceriamentioning
confidence: 99%
“…A total of twelve articles were analyzed [6][7][8][9][10][11][12][13][14][15][16][17], of which ten are devoted to the use of different techniques for creating the stable polymer microsphere/colloidal QDs hybrid structures [6][7][8][9][10][11][12][13][14][15] and two articles are devoted specifically to sensors of temperature [16,17]. It is need to point out, that one of them [16] What about our research group, it is necessary to mention the two publications [18,19], preceding the development of the model of the nanoscale biosensor of temperature presented in this article.…”
Section: Physbiosymp17mentioning
confidence: 99%